2021
DOI: 10.1002/adma.202103609
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Epitaxial Film Growth of van der Waals Ferromagnetic Ternary Chalcogenides

Abstract: non-vdW crystals (such as Mn 3 Si 2 Te 6, [12,13] ) has led to an interesting arena for studying fundamental 2D magnetism and provided numerous opportunities for 2D magnetic, magnetoelectric, and magnetooptic applications. [14,15] Electrical control of both charge and spin degrees of freedom in 2D ferromagnetic semiconductors is an important step in creating novel spintronic devices. As a single integrated platform, the spintronic devices based on these materials are expected to complement or outperform (in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…The magnetic moments of Fe1, Fe2, and Fe3 are calculated as ≈0.88, 1.64, and 1.44 µB, respectively (Figure 6b). The average net magnetic moment of Fe 5 Se 8 is ≈1.30 µB, comparable to that of Cr 2 Si 2 Te 6 and Mn 3 Si 2 Te 6 (1.02 µB/Cr, 1.80 µB/Mn, respectively), [ 56 ] indicating the strong ferromagnetism in Fe 5 Se 8 . The FM ordering in Fe 5 Se 8 leads to the asymmetric density of states for the spin‐up and spin‐down components, as shown on the projected density of states, onto the three types of Fe atoms with the two spin components (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic moments of Fe1, Fe2, and Fe3 are calculated as ≈0.88, 1.64, and 1.44 µB, respectively (Figure 6b). The average net magnetic moment of Fe 5 Se 8 is ≈1.30 µB, comparable to that of Cr 2 Si 2 Te 6 and Mn 3 Si 2 Te 6 (1.02 µB/Cr, 1.80 µB/Mn, respectively), [ 56 ] indicating the strong ferromagnetism in Fe 5 Se 8 . The FM ordering in Fe 5 Se 8 leads to the asymmetric density of states for the spin‐up and spin‐down components, as shown on the projected density of states, onto the three types of Fe atoms with the two spin components (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the foremost challenge for 2D spintronic IMDs is the preparation of large-area room-temperature vdW magnets. Although some studies have reported the wafer-scale growth of Fe 3 GeTe 2 and Cr 2 Ge 2 Te 6 , [175,176] their Curie temperatures are considerably below room temperature. Wang et al [177] first demon strated that the epitaxial growth of Fe 3 GeTe 2 on Bi 2 Te 3 could significantly increase the Curie temperature up to 400 K via interfacial exchange coupling.…”
Section: Methodsmentioning
confidence: 99%
“…Copyright 2019, Rights Managed by Nature Publishing Group. (d, e) Reprinted with permission from ref . Copyright 2021 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Vapor-phase Synthesismentioning
confidence: 99%
“…The epitaxial relationship of the initial M x C y crystal domains with the substrate enabled unidirectional alignment of the synthesized thin film; hence, single-crystal thin film formation over the entire substrate was facilitated. In another study, Giri et al recently demonstrated the epitaxial wafer-scale thin film growth of 2D ferromagnetic ternary crystals, such as Cr 2 Ge 2 Te 6 , Cr 2 Si 2 Te 6 , Mn 3 Si 2 Te 6 , etc . The epitaxial growth was achieved by flux-controlled surface diffusion of Te into a Cr or Mn metal film that was predeposited on the conventional wafer substrates (Ge, Si).…”
Section: Vapor-phase Synthesismentioning
confidence: 99%